Aspects of applied geography - Martin Duddin (Hodder and Stoughton, 1994)
This book looks in detail at the distribution and characteristics of regional landscapes in Britain and changes, co-operation and conflict in rural land use. In-depth case-studies of glaciated upland, a scarp and vale landscape, and upland limestone provide stimulating material for the examination of the human and physical factors involved in landscape evolution and the economic and social opportunities of rural land resources